Relationship Between Social Skills and Adjustment in First Year Students at Boarding School: Hubungan antara Ketearmpilan Sosial dan Penyesuaian Diri pada Santriwati Tahun Pertama di Pondok Pesantren - Ana Bidayatus Shofi; Effy Wardati Maryam (Academia Open, 2022)
This study investigates the association between social skills and self-adjustment in first-year female students. The research was conducted with a sample of 155 students at Al Hadi Islamic Boarding School in Padangan Bojonegoro. The data was collected using Likert scales to measure social skills and self-adjustment. Quantitative analysis was performed using SPSS 26.0 for Windows. The findings revealed a significant positive relationship (rxy = 0.763, p < 0.001) between social skills and self-adjustment. Higher levels of social skills were associated with greater self-adjustment, while lower social skills corresponded to lower levels of adjustment. These results emphasize the importance of social skills in fostering self-adjustment among first-year female students. This study contributes to the understanding of factors influencing student well-being and offers implications for educational interventions aimed at enhancing social skills and promoting successful adjustment in academic settings. Highlights: Positive relationship: The study reveals a significant positive relationship between social skills and self-adjustment in first-year female students, highlighting the importance of social skills in facilitating successful adjustment. Sample and methodology: The research is based on a quantitative correlation study conducted with 155 first-year female students using the Likert scale, employing SPSS 26.0 for Windows for data analysis. Implications for interventions: The findings underscore the significance of promoting social skills among students, as higher social skills are linked to better self-adjustment. These results have implications for designing educational interventions to support students' well-being and successful adaptation in academic environments. Keywords: social skills, self-adjustment, first-year female students, quantitative correlation, Likert scale.